Weight Loss in Underserved Patients — A Cluster-Randomized Trial - Katzmarzyk, Peter T; Martin, Corby K; Newton, Robert L; Apolzan, John W; Arnold, Connie L; Davis, Terry C; Price-Haywood, Eboni G; Denstel, Kara D; Mire, Emily F; Thethi, Tina K; Brantley, Phillip J; Johnson, William D; et al. (The New England journal of medicine, 2020)
In this cluster-randomized trial, carried out in an underserved population, the authors hypothesized that a high-intensity lifestyle intervention would result in greater weight loss than usual care. Patients assigned to the high-intensity program lost significantly more weight than patients who received usual care.